Vitamin D has an effect on airway inflammation and Th17/Treg balance in asthmatic mice. Issue 12 (30th August 2021) - Ma, Jing‐Guo; Wu, Guang‐Ji; Xiao, Hong‐Li; Xiao, Yan‐Min; Zha, Lin
Abstract: Asthma is regarded as a chronic inflammation of the airway. Research has highlighted the significance of Vitamin D in asthma. This study explored the mechanism of vitamin D on asthma. The asthma mouse model was established by ovalbumin (OVA) sensitization and treated with vitamin D (50 or 100 ng/ml). The morphological changes of the airway were observed by HE staining. The serum IgE contents and MDA, ROS, and SOD expressions in the bronchoalveolar lavage fluid (BALF) were detected by ELISA. The Th17 and Treg cells were detected using flow cytometry. The RORγt and Foxp 3 expressions were detected by Reverse transcription quantitative polymerase chain reaction (RT‐qPCR). IL‐17, IL‐10, and TGF‐β1 expressions were detected using ELISA. The NF‐κB pathway was blocked using the NF‐κB pathway inhibitor, Andrographolide sulfonate. The NF‐κB pathway‐related indexes were detected by western blotting. After blockade of the NF‐κB pathway, the IL‐17, IL‐10, and TGF‐G1 expressions were detected. OVA‐sensitized asthma induced airway remodeling and elevated IgE content in mice, which was downregulated after vitamin D treatment. MDA and ROS were upregulated and SOD was downregulated in asthmatic mice, while vitamin D inverted the changes. Th17/Treg ratio was imbalanced, RORγt and IL‐17 were upregulated, and Foxp 3, IL‐10, and TGF‐β1 were downregulated after OVA sensitization, while vitamin D treatment inverted these changes and inhibited the NF‐κB‐p65 phosphorylation level. After blockade of the NF‐κB pathway, IL‐17 was downregulated and IL‐10 and TGF‐β1 were upregulated. In conclusion, vitamin D rectified the Th17/Treg balance and alleviated airway inflammation by inhibiting the NF‐κB pathway in asthmatic mice.